Direct seeded rice using Drum Seeder - CGIAR Research Program on Rice (2019)
This innovation is under on-station evaluation in Mbe, Bouake. In the demonstration of the DSR with Drum seeder, farmers are very excited to adopt it as it significantly saves crop establishment cost, reduces weed management as generally herbicide molecules are applied to control weed and reduces labor use.